STUDY ON THE PROPOSALS OF ENVIRONMENTAL EDUCATION IN THE CURRICULUM DOCUMENT OF THE STATE OF GOIÁS (DC-GOEM) FOR THE NEW HIGH SCHOOL - Dores, Jeovana Teodoro das; Tavares , Giovana Galvão (CIPEEX, 2022)
THE OBJECTIVE OF THIS WORK IS TO REFLECT ON THE THEME OF ENVIRONMENTAL EDUCATION IN THE NATIONAL COMMON CURRICULAR BASE, SPECIFICALLY, HOW THE THEME IS TREATED IN THE CURRICULAR DOCUMENT FOR GOIS - DC-GOEM FOR THE NEW HIGH SCHOOL FROM THE FOLLOWING QUESTIONS: 1. WHAT IS THE PROPOSAL? OF THE DOCUMENT (BNCC/DC-GOEM) FOR THE NEW HIGH SCHOOL? WHAT’S NEW IN THE DOCUMENT? HAVE THERE BEEN ADVANCES? WERE THERE SETBACKS? WHAT IS EXPLICITLY DISCUSSED? IS THERE AN IMPLIED ASPECT? WHY SHOULD ENVIRONMENT/ENVIRONMENTAL EDUCATION OCCUPY MORE SPACE IN CURRICULAR PROPOSALS? WHAT IS THE FORMATIVE AND INFORMATIVE IMPORTANCE OF THIS THEME? SUCH QUESTIONS ARE DISCUSSED IN THE COURSE OF THIS WORK, SEEKING TO UNDERSTAND FROM HISTORICAL, SOCIAL, CULTURAL AND ECONOMIC ASPECTS TO THE NEED TO GUARANTEE THIS DISCUSSION AS A RELEVANT ASPECT OF TRAINING FOR A CRITICAL AND RESPONSIBLE CITIZEN CONSCIENCE.